The Prerequisites for Educational Training of Specialists in Economics and Entrepreneurship on the Basis of Mathematical Statistics Knowledge - Kovalchuk, V. A.; Kovalchuk, T. M. (Bìznes ìnform (Multilingual ed.), 2021)
According to the purpose of the article, which is aimed at substantiating the compliance of the acquired competencies of higher education applicants in the field of economics and entrepreneurship with the content and the amount of program knowledge in mathematical statistics, a number of publications on this issue are analyzed. The existing competency-based approaches and peculiarities of training mathematics, as well as the essence of propedeutic knowledge and requirements for their subject matter are highlighted. The narrowed application of propedeutic knowledge and the lack of a systematic approach, taking into account interdisciplinary connections, are indicated. On the basis of the educational and professional program «Entrepreneurship, trade and exchange activities» the content of the working program of the discipline «Quality Management, standardization and certification» is analyzed. The essential tasks of the discipline are determined using statistical methods for the control and management of quality of products and services that require deep knowledge about mathematical statistics. The mechanism of establishing compliance of basic knowledge of the subject matter in mathematical statistics with applied tasks of quality management is proposed. The authors have elaborated the algorithms of systematization, evaluation and analysis of sampled data together with determination of type and parameters of their statistical distribution, corresponding to the main tasks of mathematical statistics. The presented algorithm of research is accompanied by visual diagrams, which step by step reflect the course of solving statistical tasks with the relevant formulas, tables and recommendations, which contributes to better and more conscious assimilation of the material. On the example of studying a particular professional discipline, a systematic methodical approach to the formation of propedeutic knowledge of an interdisciplinary nature with the setting of tasks in certain types of economic activity is substantiated. It is proposed to extend the use of developed approaches to other areas of knowledge in the sphere of education.